Republicanism-Based Budgeting: Politik Kewargaan dan Resistensi Terhadap Neoliberalisme dan Oligarki - Abjan, Gustamin; Djamhuri, Ali; Roekhudin (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: This research aims to establish the concept of republicanism-based public budgeting as an alternative to mainstream public budgeting that exists in the era of neoliberalism and predatory oligarchic domination. Methodology/approach: This research uses a qualitative method based on a critical paradigm. Analysis of the political economy structure of oligarchy and neoliberalism is used to analyze how the power relations of predatory oligarchy and neoliberalism in public budgeting in Indonesia. In addition, the philosophical framework of republicanism is used to construct an alternative to public budgeting that is free from the hegemony of predatory oligarchy and neoliberalism. Findings: Republicanism-based budgeting has particularities that are different from mainstream public budgeting. These features include virtue, citizen participation and freedom, and patriotism. This value is the main force to resist and negate the various interests of neoliberalism and predatory oligarchy (resprivata) that have taken root in the public budgeting arena (respublica). Practical implications: Actors involved in public budgeting should not only focus on aspects of efficiency but need to consider the values of social justice, meaningful participation of citizens and upholding the public spirit of the common good. In addition, public budgeting needs to be infused with various republican values such as civic politics, patriotism and benevolence as an effort to strengthen and nurture solidarity and a sense of citizen ownership of the public budget. Originality/value: Based on the philosophy of republicanism, this study contextualises various authentic ideas of republicanism to construct public budgeting.